Serious Games and Game Performance Before and During the Israel-Hamas War: The Case of Fact Finders and PeaceMaker - Ronit Kampf; Nicolaidou, Iolie (My University, 2025)
This study examines the impact of players’ gender and nationality on game performance before and during the Israel-Hamas war. The study focuses on two games for social impact revolving around intractable conflicts: PeaceMaker (Israeli-Palestinian conflict) and Fact Finders (Cyprus Conflict). We conducted three case studies with 510 undergraduates voluntarily playing the aforementioned games and reporting their final scores. The participants included Israeli-Jew, Palestinian, American, and Cypriot undergraduate students. We found that before the Israel-Hamas war, women won PeaceMaker no less than men. Interestingly, during the Israel-Hamas war, women won PeaceMaker more than men. Finally, third-parties to the Cyprus conflict (Israelis, Palestinians and Americans) significantly outperformed direct-parties (Cypriots) in Fact Finders before and during the Israel-Hamas war. Overall this study's findings suggest that serious games can be used as effective interventions for peace education and conflict resolution regardless of players’ gender or nationality, even during violent times.